Land taxes in a Latin American context - Juliano J. Assunç\~ao; Humberto Moreira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
Since Henry George (1839-1897) economists have been arguing that a tax on unim- proved land is an ideal tax on e ciency grounds. Output taxes, on the other hand, have distortional eects on the economy. This paper shows that under asymmetric information output tax might be used along with land tax in order to implement the optimal taxation scheme in a Latin-American context, i.e., in an economy with imperfect land-rental market, non-agricultural land use and non-revenue objectives of land taxation. Also, we show that: (i) schemes based on land taxes alone might not be implementable; and (ii) tax evasion is more acute among large landholders.
Keywords: 330; Optimal taxation; tax evasion; land use.; Grundsteuer; Optimale Besteuerung; Steuervermeidung; Theorie; Lateinamerika